BTK, the new kid on the (oncology) block? - Grassilli, Emanuela; Cerrito, Maria Grazia; Lavitrano, Marialuisa (Frontiers in Oncology, 2022)
In the last decade data piled up indicating that BTK – for twenty years considered as a “private matter” of bone marrow-derived cells – it is expressed and plays important and different roles also outside of the hematopoietic compartment and, most notably, in tumor cells. Initial evidence that BTK plays a critical role in B cell-derived malignancies prompted the chase for specific inhibitors, the forefather of which entered the clinic in a record time and paved the way for an ever increasing number of new molecules to be trialed. The growing interests in BTK also led to the discovery that, in solid tumors, two novel isoforms are mainly expressed and actionable liabilities for target therapy. Remarkably, the different isoforms appear to be involved in different signaling pathways which will have to be attentively specified in order to define the area of therapeutic intervention. In this perspective we briefly summarize the progress made in the last decade in studying BTK and its isoforms in cancer cells and define the open questions to be addressed in order to get the most benefits from its targeting for therapeutic purposes.